Churchill's secret war the British empire and the ravaging of India during World War II - Mukerjee, Madhusree (New York Basic Books, 2010)
Examines Winston Churchill's efforts to defeat the freedom movement in India during World War II, comparing his actions in Europe to the decisions he made between 1940 and 1944, which resulted in the deaths of more than three million men, women, and children in India.
Prologue: Our title to India -- Empire at war -- Harvesting the colonies -- Scorched -- At any price -- Death of a thousand cuts -- An occupied and starving country -- In the village -- On the street -- Run rabbit run -- Life after death -- Split and quit -- The reckoning.
Includes bibliographical references (p. 283-319).
Keywords: Churchill, Winston -- 1874-1965.; World War, 1939-1945 -- Influence; Famines -- India -- Bengal; Great Britain -- Foreign relations -- India; India -- Foreign relations -- Great Britain; India -- History -- 20th century; Great Britain -- Colonies -- History -- 20th century